Maternal factors influencing birth weight of term babies among women who received antenatal care at a Nigerian voluntary agency health care facility - Olafimihan, Victoria I.; Ariba, Adekunle J.; Egunjobi, Ademola; Abiodun, Olusanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Birthweight is an important indicator of babies’ health status and a reliable predictor of their postnatal survival. Maternal factors are regarded as major contributors to birthweight outcome due to their direct effects on foetal growth. Proper knowledge of these factors is essential for implementing preventive measures against suboptimal birthweight. Objective of the study sought to determine the proportion of term babies with normal birthweight and identify the maternal factors that influence birthweight. Methods: This cross-sectional study was conducted on 257 booked pregnant women and their newborns delivered at the Sacred Heart Hospital (SHH), Abeokuta, Nigeria between August and November 2017. Selection was by systematic random sampling method. Data were collected with a pre-tested interviewer-administered questionnaire and analyzed with SPSS version 21 program. Results: The mean age of the women was 30.73±5.17 years. Among the women, 95.7% had at least senior secondary education, 95% of them were married and employed. The mean birthweight was 3.25±0.47 kg and male babies had higher mean weight (male: 3.30±0.54 kg; female: 3.21±0.39 kg). NBW was recorded among 92.6% of the babies with 3.5 and 3.9% as LBW and HBW, respectively. Only maternal booking BMI (p=0.005) and chronic hypertension (p=0.007) were significantly associated with birthweight. Conclusion: Most babies in this study had normal birthweights reflecting the influence of optimal maternal biological and socio-demographic characteristics. Chronic hypertension and subnormal booking BMI undermined achievement of optimal birthweight, underscoring the need for pre-conception care for intending mothers.